Effects of Extreme Dilutions of Preparations on Gene Expression Profiles of Human Cells - Elisabetta Bigagli; Cristina Luceri; Andrea Dei; Simonetta Bernardini; Piero Dolara (SAGE Publishing, 2016)
Gene expression analysis has been employed in the past to test the effects of high dilutions on cell systems. However, most of the previous studies were restricted to the investigation of few dilutions, making it difficult to explore underlying mechanisms of action. Using whole-genome transcriptomic analysis, we investigated the effects of a wide range of Apis mellifica dilutions on gene expression profiles of human cells. RWPE-1 cells, a nonneoplastic adult human epithelial prostate cell line, were exposed to Apis mellifica preparations (3C, 5C, 7C, 9C, 12C, 15C, and 30C) or to the reference solvent solutions for 24 hours; nonexposed cells were also checked for gene expression variations. Our results showed that even the most diluted solutions retained the ability to trigger significant variations in gene expression. Gene pathway analysis revealed consistent variations in gene expression induced by Apis mellifica when compared to nonexposed reference cells but not to reference solvent solutions. Since the effects of Apis Mellifica at extreme dilutions did not show dose-effect relationships, the biological or functional interpretation of these results remains uncertain.